Pengaruh Kualitas Pelayanan, Fasilitas Publik, dan Harga Terhadap Kepuasan Pengunjung Dinas Pemuda dan Olahraga Provinsi DKI Jakarta (Studi Kasus Pada Kolam Renang dan Gelanggang Olahraga Bulungan Jakarta Selatan) - Dasrul, Nesbudih; Firza, Muhammad (Neraca : Jurnal Akuntansi Terapan, 2025)
Visitor satisfaction with public spaces is influenced by various factors. Each individual has different desires and preferences.iService quality,ifacilities,i andi pricingi arei amongi thei factorsi thati affecti visitori satisfaction.i Complaintsi reflectingi dissatisfactioni amongi visitorsi toi thei Swimmingi Pooli andi Sportsi Halli ini Bulungani stilli exist.i Thei purposei ofi thisi studyi isi toi examinei thei influencei ofi Servicei Quality,i Facilities,i andi Pricingi oni visitori satisfaction.i Thei samplingi techniquei usedi isi accidentali sampling,i wherei respondentsi arei choseni basedi oni chancei encounters,i meaningi anyonei whoi happensi toi meeti thei researcheri cani bei usedi asi ai samplei ifi theyi arei deemedi suitablei asi ai datai source.i Thei totali samplei sizei usedi ini thisi studyi isi 97i respondents.i Thei resultsi ofi thei hypothesisi testingi ini thisi studyi indicatei thati servicei qualityi hasi ai positivei effecti oni visitori satisfaction,i facilitiesi havei ai positivei effecti oni visitori satisfaction,i andi pricingi alsoi hasi ai positivei effecti oni visitori satisfaction.i Simultaneously,i servicei qualityi (X1),i facilitiesi (X2),i andi pricingi (X3)i collectivelyi influencei visitori satisfactioni (Y)i byi 45.4%,i whilei thei remainingi 54.6%i isi influencedi byi otheri factors.